ANALISIS PENGARUH PENGGUNAAN CAMPURAN PERTAMAX DAN METANOL TERHADAP KONSUMSI BAHAN BAKAR DAN EFISIENSI EKONOMI KENDARAAN - Daulay, Waddi Elman Syah Putra; Andrizal, Andrizal; Maksum, Hasan; Rifdarmon, Rifdarmon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to analyze the effect of Pertamax and methanol blends on fuel consumption and economic efficiency of a Honda Beat Street 110 cc motorcycle. The research employed a quantitative experimental method using the Taguchi approach, with four factors: fuel blend percentage (0%, 10%, 20%), engine speed (2000 rpm, 2500 rpm, 3000 rpm), vehicle speed (40 km/h, 60 km/h, 80 km/h), and engine temperature (70 °C, 90 °C, 110 °C). The results showed that the lowest fuel consumption was achieved with 0% methanol at 2500 rpm and 90 °C, recording 0.1378 ml/s, while the highest consumption occurred with 20% methanol at 2000 rpm and 90 °C, reaching 0.2500 ml/s. In terms of economic efficiency, the optimal condition was obtained with 10% methanol, 2500 rpm, 80 km/h, and 70 °C, resulting in the lowest operational cost of IDR 8,646/km. Thus, blending Pertamax and methanol at certain proportions can improve vehicle economic efficiency and serve as an alternative to reduce fuel expenses.Keywords: Pertamax, Methanol, Fuel Consumption, Economic Efficiency, Taguchi